1995
DOI: 10.1111/j.1365-2125.1995.tb04467.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral sumatriptan, a 5‐HT1 receptor agonist, on circulating ACTH and cortisol concentrations in man.

Abstract: 1 The effects of oral sumatriptan (50, 100 and 200 mg), a 5-HT1 receptor agonist, and placebo, on circulating adrenocorticotrophic hormone (ACTH) and cortisol concentrations were determined over 24 h after dosing, in 26 healthy male subjects. ACTH was measured by immunoradiometric assay and cortisol by radioimmunoassay. 2 After sumatriptan all subjects displayed a normal diurnal rhythm for circulating ACTH and cortisol compared with placebo. 3 There was a reduction in the trough circulating ACTH concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…The lack of effect of sumatriptan on the cortisol response observed in the present study is contrary to previously reported data that showed a reduction in plasma cortisol after acutely administered sumatriptan to healthy volunteers at rest (Entwisle et al, 1995; Gross-Isseroff et al, 2004; Pinessi et al, 2003). However, there is also one study that showed no changes in cortisol plasma levels after sumatriptan intake (Boeles et al, 1997).…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of effect of sumatriptan on the cortisol response observed in the present study is contrary to previously reported data that showed a reduction in plasma cortisol after acutely administered sumatriptan to healthy volunteers at rest (Entwisle et al, 1995; Gross-Isseroff et al, 2004; Pinessi et al, 2003). However, there is also one study that showed no changes in cortisol plasma levels after sumatriptan intake (Boeles et al, 1997).…”
Section: Discussioncontrasting
confidence: 99%
“…14,15 Finally, triptans increase GH and reduce cortisol, ACTH, and prolactin plasmatic concentrations after acute administration both in patients with episodic migraine and healthy volunteers. 16,17 In experimental animals, chronic administration of triptans causes a downregulation of the 5-HT 1B/D receptors involved in hormonal secretion, and influences serotonin synthesis in various brain regions. 18,19 The same mechanisms account for the regulation of COX-1 and COX-2 enzymes, which are the main pharmacological targets of NSAIDs.…”
Section: And Itmentioning
confidence: 99%
“…Protracted administration of acetylsalicylic acid and indomethacin, 2 NSAIDs commonly used as abortive antimigraine agents, causes a significant rise in GH concentrations and reduces ACTH release 14,15 . Finally, triptans increase GH and reduce cortisol, ACTH, and prolactin plasmatic concentrations after acute administration both in patients with episodic migraine and healthy volunteers 16,17 . In experimental animals, chronic administration of triptans causes a downregulation of the 5‐HT 1B/D receptors involved in hormonal secretion, and influences serotonin synthesis in various brain regions 18,19 .…”
mentioning
confidence: 99%
“…Sumatriptan is a selective 5HT 1B/1D receptor agonist effective in the treatment of CH attacks (12). Several studies in healthy volunteers have shown that the drug induces a significant increase in growth hormone (GH) plasmatic concentrations and a reduction of prolactin (PRL), adrenocorticotropic hormone (ACTH) and cortisol secretion (13)(14)(15). Studies in experimental animals have shown these effects are mediated through the activation of hypothalamic 5-HT 1D receptors (16).…”
Section: Introductionmentioning
confidence: 99%